AN INTEGRATED TECHNOLOGY ACCEPTANCE MODEL FOR SMART CITY MOBILE APPLICATIONS: IDENTIFICATION OF KEY FACTORS AND EXTENSION OF TECHNOLOGY ADOPTION - Musab Talha Akpınar; Mehmet Atak (International Journal of Management Studies)
Smart cities have experienced significant improvements in service quality, resident satisfaction, sustainability, and economic development through the application of information and communication technology. With urban populations expected to grow, the adoption of smart city mobile applications (SCMA) can enhance the efficiency and impact of urban regions. This research explores the cognitive factors influencing user engagement and adoption of SCMA, by integrating identified factors with technological adaptation models. The decision of individual users to embrace such as SCMA has garnered attention from both information systems (IS) researchers and industry practitioners. Key factors affecting SCMA user acceptance include perceived enjoyment, innovation, trust, social influence, security, compliance, satisfaction, perceived benefit, ease of use, and intention to use. Data was analyzed using a structural equation model (SEM), with participants responding to questionnaire items on a five-point Likert scale. Out of an initial 1,142 responses, 1,062 valid samples were included in the final analysis after data filtering, achieving a response rate of 67 percent. Enhanced user satisfaction is crucial for the success of SCMA providers. The industry must allocate additional resources toward developing robust and reliable infrastructures and platforms that enhance mobility and service quality. To drive the future of Web 3.0, the industry must also address long-term challenges, such as creating new universal systems and environments. The conclusion of this study is discussed with respect to both theoretical and practical implications.